Resultados experimentales del cohete aeroespacial JICAAT, Ayacucho-Perú - Huayanay Villar, José Luis (2025)
Villa Automation S.A.C is developing an advanced engineering project related to rockets, specifically the JICAAT rocket (International Conference on Advanced Sciences of Astrodynamics and Remote Sensing). Villa Automation is working on an ambitious project that combines aerospace engineering, automation, and data analysis to develop a functional rocket. Despite current technical challenges, such as engine failures, this project represents an important step towards the advancement of space technology in the region. This project encompasses the development of efficient propulsion systems, although they face challenges such as propulsion engine failures (e.g., explosions). Optimization of flight systems to ensure stability and control during launch. Control Systems and Sensors: Use of orientation data (Pitch, Roll, Yaw) to monitor and adjust the rocket's attitude in real time. Implementation of sensors to record positions (PosX, PosZ) and trajectories, helping to analyze the rocket's behavior in flight. The Villa Automation team has been working hard on developing the engine for the JICAAT I and II rocket, which is a solid-fuel engine. It produces constant and sustained emissions with slight oscillations that could be related to thrust or turbulence control.